A geografia do crime : territorialização dos principais crimes e a influência do comércio ilegal, no tráfico e no consumo de drogas nsa cidade de Catalão (GO) - Rosa, Aline Hubaide (2015)
Crime is now one of the biggest social problems with which the Brazilian society lives. It comes as a serious issue because it reaches all Brazilian and exposes too important to risk legal interests, such as property, physical integrity, peace, and even life. So, we have to study that might encourage understanding of the ways in which crime occurs at facilitating the prevention and combat. The crime stems from a social relationship, occurring in certain areas. The same has its expansion and virtually origin in the cities and in them settled territories where they are practiced. Therefore, this study aimed to understand the relationship between town and crime. For this, the city of Catalão (GO) located in the southeastern state of Goias and in central Brazil, midsize, and thriving economic and social situation has been chosen as the object of study of this work. To carry out the analysis were determined eight years of occurrence of the five major crimes. Between the period 2006-2013 the theft offenses, theft, threat, murder, drug trafficking and its derivatives were studied, and this has been possible through the data obtained from the database of the Civil Goiás state police. The most frequent studies crimes in the city during the analysis period allowed the understanding that the shape and profile of the crimes that most occur change with time, and has allowed to view the relationship among all other crimes to trafficking in narcotic perhaps the most current social problem in Brazil. Thus, it was still considered as trade in narcotics occurs in the city of Catalan and how this crime is incorporated in the urban space and modifies the daily life of society. During the study, we understand that the crime mapping tool furthers our understanding of the occupation of these in urban areas and collaborates with practical prevention and combating of crime, making it a great ally of the police and political bodies responsible for public security in the country.